Use of social networking sites (SNSs) and its repercussions on sleep quality, psychosocial behavior, academic performance and circadian rhythm of humans - a brief review - Kumar Swain, Rakesh; Pati, Atanu Kumar (Biological rhythm research, 2021)
Social networking sites (SNSs) confer countless benefits to mankind through increased communication and connection between and among millions of people on the globe. Do the detrimental effects of SNSs outweigh its benefits? We have tried to answer this question through reviewing the relevant literature on the repercussions of use of SNSs on sleep quality, psychosocial behavior, academic performance and circadian rhythm in humans. Literature on the subject underscores the adverse effects of SNSs usage on sleep resulting in poor sleep quality, delayed sleep onset, shortening of sleep length, excessive daytime sleepiness (EDS), insomnia, apnea and nightmare. The students addicted to social media suffer from psychiatric distress, anxiety, depression, low self-esteem, suicidal ideation, procrastination and poor academic attainment. There is, however, a paucity of literature on the effects of overuse of SNSs on the functioning of circadian clocks in humans. It emerged that the adolescents and young adults are the most vulnerable to the ill effects of excessive use of the SNSs. We recommend that more researches on the effects of SNSs on human health should be carried out and effective awareness campaigns should be launched to educate the people about the darker side of the excessive use of SNSs.